Toward a Fundamental Understanding of the Role of Lignin in the Biorefinery Process - Yao, Lan; Yang, Haitao; Meng, Xianzhi; Ragauskas, Arthur J. (Frontiers in Energy Research, 2022)
As one of the main components in biomass, lignin plays a vital role in the biorefinery industry. Its unique structural feature increases the dose of cellulase during deconstruction and is an attractive resource for many high valued products. The inhibition of lignin on cellulase is proposed to occur in several ways, with the most studied being nonproductive enzyme binding, which is attributed to hydrogen bonding, hydrophobic and/or electrostatic interactions. This review provides a comprehensive review of how lignin is transformed during various pretreatment methods as well as how these changes impact the cellulase inhibition. Future pretreatment directions for decreased cellulase inhibition are also proposed.